+0  
 
0
225
1
avatar

sec^6(x)[sec(x)tan(x)] -sec^4(x)[sec(x)tan(x)] = sec^5(x)tan^3(x)


thanks.

Guest Jun 4, 2017
 #1
avatar+7155 
+1

sec6(x) sec(x) tan(x)  -  sec4(x) sec(x) tan(x)

 

=  sec7(x) tan(x)   -   sec5(x) tan(x)               Factor out   sec5(x) tan(x)   .

 

=  sec5(x) tan(x) * ( sec2(x)  -  1 )                 Rewrite secant as 1/cosine

 

= sec5(x) tan(x) * ( 1/cos2(x)  -  1 )               Get a common denominator and combine the fractions.

 

= sec5(x) tan(x) * ( 1/cos2(x)  -  cos2(x)/cos2(x) )

 

= sec5(x) tan(x) * ( [ 1 -  cos2(x) ] /cos2(x) )    Rewite   1 - cos2(x)   as   sin2(x)

 

= sec5(x) tan(x) * ( sin2(x) /cos2(x) )

 

= sec5(x) tan(x) * tan2(x)

 

= sec5(x) tan3(x)

hectictar  Jun 4, 2017

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.